Gambaran hasil Pemeriksaan Kadar Kalsium (CA) Pada Wanita Menopause di Hartaco Indah Kota Makassar - Ansar ansar; Rizman Naim; Muhajirah Mustafa (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2018)
Calcium is one of the minerals that plays a very important role in the human body. Calcium also acts as a process of bone and tooth formation and measures the biological processes in the body, menopause is a transition period from the reproductive period to the non-reproductive period that occurs due to decreased generative function or estrogen hormone from the ovary. This study aims to determine the description of venous blood calcium in postmenopausal women and to determine the description of venous blood calcium in menopausal women. This type of research is descriptive which aims to determine the picture of calcium in menopausal women aged 45-50 years. From the results of analysis on 10 samples Describe that there are 3 samples of calcium levels in Menopouse women in the Normal Category and 7 samples in the Decreasing Category. So that it can be concluded that calcium levels in Menopause women are 45-50 years old. That is, the older the age, the lower the calcium levels in the body.